Human-Elephant Conflict and Mitigation Measures in Jhapa District, Nepal - Neupane, Bijaya; Budhathoki, Subash; Khatiwoda, Binod (Journal of Forest and Livelihood, 2018)
Asian elephants are the largest terrestrial animals that are highly threatened due to habitat loss and fragmentation. Human - Elephant Conflict (HEC) is a complex interaction between human and elephant, which represents detrimental impacts for both. The aim of this study was to explore HEC in terms of human casualties and injuries and crop and property damage in all the wards of Jalthal Village Development Committee of Jhapa district, Nepal. It also aimed at identifying the commonly practiced mitigation measures by the local people in the study area. For this study, 179 households were randomly selected for questionnaire surveys followed by 20 key informant interviews and 5 focus group discussions. Our study shows that the settlements located nearby the Jalthal forest had higher risks of elephant attacks. The crop damage was the most frequent damage in terms of HEC in the study area. Among the crops, paddy was the most damaged crop. Property damage was the second problem faced by the local people. However, there were no significant differences in crop and properties damaged by elephants among different socio-economic classes. The most commonly used mitigation measures adopted in the study area were shouting and use of fire but people were not satisfied with the present conflict management strategies due to their ineffectiveness. This study implies that the presence of resident wild elephant has increased the vulnerability of local people living around the Jalthal forest. Thus, detail study on the habitat assessment and seasonal movement patterns of resident herds in and around Jalthal forest area is required for proper planning and implementing suitable mitigation measures and habitat management activities.